Molting characteristics of crossbreds between Alabio and Pekin ducks - T, Susanti; LH, Prasetyo (Indonesian Animal Sciences Society, 2015)
Molting is a problem for duck farmers, during which the ducks stop laying eggs. Molting characteristics may be altered through crossing between non-molting to molting ducks. The purpose of this study was to evaluate molting characteristics of the crossing between Alabio and Pekin ducks. The materials used were 90 female AP (Alabio males x Pekin females) and 90 female PA (Pekin males x Alabio females), 25 female Alabio and 25 female Pekin ducks. The ducks were housed in individual cages at the Indonesian Research Institute for Animal Production, Ciawi Bogor. Variables measured were the length of molting and egg production in 30 weeks, data were analyzed using ANOVA and followed by the estimation of the value of heterosis. Result showed that the molting of Pekin ducks was 71.31±9.36 days, it was longer than Alabio, AP or PA ducks, which were respectively 42.44±8.59, 43.63±4.88 and 49.35±4.85 days (P<0.01). Egg production of Pekin duck (56.41±4.59) was significantly lower (P<0.01) than that of Alabio, AP or PA, which were 72.48±3.24, 83.75±1.39 and 76.12±1.68 respectively. The heterosis of molting period of AP was higher than that of PA (-23.29 vs -13.23%). The heterosis of egg production of AP was higher than PA (29.96 vs 18.12%). It is concluded that the AP crossbred could be utilized as the initial population to produce a superior line characterized by high egg production and controllable molting. Key Words: Duck, Alabio, Pekin, Crossbreds, Molting